Serum antibodies to pneumolysin in patients with pneumonia. - Kanclerski, K (1988)
Serum antibodies to purified pneumolysin were determined by enzyme-linked immunosorbent assay (ELISA) in paired samples from 406 adult patients with community-acquired pneumonia and in samples from 184 healthy controls. A high sensitivity (83%) was obtained in patients with blood culture-confirmed pneumococcal pneumonia. In patients with a tentative pneumococcal diagnosis based on culture of samples from the sputum or the nasopharynx, 45% were positive by ELISA. The difference likely reflected the different relevance of cultural findings for the diagnosis of pneumococcal pneumonia. A significant rise in ELISA titer was found in 17% of the patients. When the diagnosis was also based on high titers, 25% were positive. Pneumococcal pneumonia diagnosed by the pneumolysin ELISA was significantly more common in the patients with a more severe disease and who required hospitalization (21 versus 5% for outpatients). Younger patients were more often positive for pneumococci as determined by high titers, while older patients showed titer rises. Mixed infections with other infectious agents were not uncommon. The finding of low titers in acute-phase samples from positive patients and in the youngest and oldest age groups of healthy controls were unexpected, indicating that further studies on the role of pneumolysin in pneumococcal disease are warranted.